Mechanical trading systems : pairing trader psychology with technical analysis - Weissman, Richard L. (Wiley trading., 2005)
A wide variety of flexible trading systems that combine sophisticated technical analysis with trading psychology theory Mechanical Trading Systems examines the development process for choosing and using mechanical trading systems in conjunction with trader psychology.